Anti-Ma2/Ta antibodies in a woman with primary lateral sclerosis-like phenotype and Sjögren syndrome - Piccolo, Giovanni; Tavazzi, Eleonora; Jarius, Sven; Alfonsi, Enrico; Cavagna, Lorenzo; Piccolo, Laura; Zardini, Elisabetta; Voltz, Raymond; Franciotta, Diego (Neurological sciences, 2011)
Anti-Ma2/Ta antibodies are rare paraneoplastic antibodies, which are mostly associated with limbic encephalitis in male patients with testicular cancer. We report on a 50-year-old woman with a pure progressive spastic paraparesis. Next, she was diagnosed as having a Sjögren syndrome, with serological positivity for anti-SS-Ro antibodies. The patient’s serum and cerebrospinal fluid samples were positive for anti-Ma2/Ta antibodies, which were also proved to be intrathecally produced. These findings, and the coexistence of systemic autoimmunity, led us to treat the patient with corticosteroids first, and then with plasma exchange. Neurological symptoms scarcely responded to both the therapies. The search for cancer was negative up to 4 years after the disease onset. Our case expands the spectrum of clinical syndromes associated with anti-Ma2/Ta antibodies.